Effects of microalgae as dietary supplement on palatability, digestibility, fecal metabolites, and microbiota in healthy dogs - Cabrita, Ana R. J.; Guilherme-Fernandes, Joana; Spínola, Maria; Maia, Margarida R. G.; Yergaliyev, Timur; Camarinha-Silva, Amélia; Fonseca, António J. M. (Frontiers in Veterinary Science, 2023)
The current trend of dog owners increasingly favoring the functional value of food to assure preventive health and wellbeing of their pets has been raising the interest in microalgae as natural additives with bioactive properties. However, scientific studies addressing the effects of microalgae supplementation in diets for dogs are scarce. This study aimed to evaluate the effects of dietary supplementation with three microalgae species (Chlorella vulgaris, Nannochloropsis oceanica and Tetradesmus obliquus) on diet palatability, total tract digestibility, metabolizable energy content, fecal metabolites and microbiota of dogs. Twelve adult Beagle dogs were used in three two-bowl tests to compare the palatability of a commercial complete diet for adult dogs without (reference diet) and with 1.5% supplementation of each microalgae. From the results obtained, three digestibility trials were performed according to a replicated Latin square 3 x 3, with six adult Beagle dogs, three experimental periods of 10 days each, and three dietary supplementation levels of microalgae (0.5%, 1.0%, and 1.5%). In each trial, effects of microalgae supplementation levels on total tract digestibility, metabolizable energy content, fecal metabolites and microbiota of dogs were evaluated. First diet approached or tasted was not significantly affected by microalgae inclusion, but dogs showed a preference for the reference diet over the diets with 1.5% inclusion of C. vulgaris and N. oceanica, no difference being observed with 1.5% T. obliquus. In all digestibility trials, dietary supplementation with microalgae up to 1.5% did not greatly affected the dietary chemical composition and kept unaffected food intake, fecal output and metabolites, and digestibility of nutrients and energy. Compared with the reference diet, supplementation with C. vulgaris increased protein digestibility. Fecal characteristics and metabolites were affected by microalgae supplementation, being the effects dependent on the species. Fecal microbiota composition of dogs fed with microalgae-supplemented diets was modified by promoting the beneficial Turicibacter and Peptococcus genera associated with gut health and activation of the immune system. Overall, the results support C. vulgaris, N. oceanica and T. obliquusas sustainable functional supplements that potentially enhance gastrointestinal health of dogs through the selective stimulation of microbiota without detrimental effects on food intake and digestibility.